Uut mien hérte : levensverhalen van inwoners uit de nieuwe stad in Oostende - Delrue, Eline; Delrue, Rik; Van den Ende, Eliane (Oostende: Rik Delrue; Samenlevingsopbouw West-Vlaanderen, 2008)
"teksten: Eline Delrue, Rik Delrue, Eliane Van den Ende ... et al."